The Influence of Principals’ Mental Health and School Climate on Teachers’ Productivity and Wellbeing in Elementary Schools of Garut Regency - Darwati, Ida; Abidin, Yunus; Sutini, Ai (Journal of Educational Sciences, 2025)
Teachers’ productivity and wellbeing are essential for ensuring the quality of education. These aspects are influenced by principals’ mental health, which shapes leadership effectiveness, and by school climate, which determines the level of support and motivation experienced by teachers. In Indonesia, limited studies have simultaneously examined the impact of these two factors on teachers’ outcomes. This study investigates the influence of principals’ mental health and school climate on teachers’ work productivity and wellbeing in public elementary schools in Garut Regency. Using a quantitative approach with canonical correlation analysis, data were collected from 175 teachers across 33 schools through structured questionnaires. The findings reveal that principals’ mental health and school climate significantly affect teachers’ productivity, while their impact on teachers’ wellbeing is weaker yet still significant. The novelty of this study lies in the application of canonical correlation analysis to examine the simultaneous relationship between leadership psychology, school climate, and teacher outcomes. The results emphasize the importance of fostering principals’ mental health and creating supportive school climates as strategic efforts to enhance teacher performance and wellbeing.